Influence of Replacement Part of Starch with Inulin on the Rheological Properties of Pastes and Gels Based on Potato Starch - Mariusz Witczak; Zofia Smółka; Teresa Witczak; Anna Stępień; Agata Bednarz (International Journal of Food Science)
The objective of the present study was to determine the influence of replacement part of starch with inulin on the rheological characteristics of pastes and gels obtained on the basis of potato starch. Replacement of the starch by inulin varied from 0 to 40%. Flow curves for pastes and gels were determined, and the viscoelastic properties were characterized using dynamic tests and creep and recovery tests. It was determined that the replacement of part of potato starch with inulin significantly modifies rheological properties of starch pastes and gels, weakening their structure. With the increasing amount of inulin, an increase of viscous properties was becoming more apparent. Moreover, an irregular influence of inulin addition on the parameters of rheological characteristics was determined. Initially, the differences were minor, and the differences at the lowest addition were typically statistically insignificant, followed by strong increase with local restrictions to structural weakening.